Comparative legal analysis of the expertise in court under the criminal law of Ukraine and CIS countries - A. N. Protsenko (Bulletin of Kharkiv National University of Internal Affairs)
A comparative analysis of the expertise during the criminal proceedings in accordance with the Criminal Procedure Code of Ukraine and the Republics of Azerbaijan, Belarus, Armenia, Kyrgyzstan, Estonia, Kazakhstan, Moldova, Tajikistan, Turkmenistan, Uzbekistan and the Russian Federation has been carried out.